Meningkatkan Kemampuan Komunikasi Matematis Siswa Menggunakan Strategi Numbered Head Together pada Siswa Kelas X-A MA Al Fattahiyyah - Evy Ramadina (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2019)
Technological development has a huge influence on the social, economic, cultural and even educational fields, especially in mathematics subject. Mathematical communication skills of students obtained in mathematics learning help train students to solve problems in everyday life. Based on our survey, mathematical communication skills of students are still relatively low, this is evident in learning to solve applied mathematics problems. Students tend to have difficulty expressing their ideas in solving problems. This study aims to determine the improvement of students' mathematical communication skills in class X-A MA Al Fattahiyyah by learning numbered head together. Class Action Research refers to John Elliot's model is proposed in this research. Subjects are students of class X-A MA Al Fattahiyyah. Data collection techniques were written tests and documentation. While the research instrument was a test of students' mathematical communication skills. Research results show that the use of numbered head together can improve students' mathematical communication skills.